EFEKTIVITAS PEMBELAJARAN MATA PELAJARAN PMKR SECARA DARING SISWA KELAS XI SMK N 1 RANDUDONGKAL PEMALANG JAWA TENGAH TAHUN AJARAN 2022/2023 - Nanda Aulia Dewi; Slamet Priyanto; Rabiman (JURNAL VOKASI DEWANTARA (JVD), 2025)
The Effectiveness of Learning PMKR Subjects Online for Class XI Students of SMK N 1 RandudongkalPemalang, Central Java, Academic Year 2022/2023. Thesis for Mechanical Engineering VocationalEducation Study Program, Faculty of Teacher Training and Education, Tamansiswa BachelorwiyataUniversity, Yogyakarta. The aims of this study are: (1) to find out how online learning is implemented;(2) factors that affect the effectiveness of learning; and (3) the level of effectiveness of learning in thePMKR subject online for class XI students majoring in Light Vehicle Engineering at SMK N 1Randudongkal. This type of research is mixed research (mixed methods). The population in this studywere students majoring in Light Vehicle Engineering at SMK N 1 Randudongkal with a sample of 34students in class XI majoring in TKR. The technique used to collect data is incidental sampling technique.The validity test was carried out using the product moment technique and the reliability test was carriedout using the Alpha Cronbach method. From the observations it was found that the implementation ofonline learning through Google meet and WhatsApp in the PMKR subject for class XI students at SMK N1 Randudongkal did not run smoothly. Factors that cause the non-current include technical factors,learning implementation factors and external factors. From the students' responses, scores were obtainedfor each factor, namely technical factors with an average index score of 67.77% (less effective), externalfactors with a score of 70.28% (less effective), learning implementation factor with a score of 72.47% (less effective). From these results it is known that the level of effectiveness of online learning in PMKRsubjects is less effective in obtaining the highest score, namely 60% (less effective) of students whoexperience obstacles during the online learning process at SMK N 1 Randudongkal Pemalang.